2017
DOI: 10.1111/acer.13566
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hazardous Alcohol Use During Pregnancy on Growth Outcomes at Birth: Findings from a South African Cohort Study

Abstract: BackgroundCohort studies have noted associations between hazardous alcohol use during pregnancy and infant growth outcomes, but many have not controlled for potential psychosocial confounders. To assess the unique contribution of hazardous alcohol use, we examined its effect on infant growth outcomes while controlling for maternal psychosocial stressors and hazardous tobacco and drug use in a cohort of 986 pregnant South African women enrolled into the Drakenstein Child Health Study between 2012 and 2015.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 42 publications
0
39
0
1
Order By: Relevance
“…In the final review, articles were published from 10 countries among 46 countries were included. Of these studies, eleven studies were found from Ethiopia [13,19,[30][31][32][33][34][35][36][37][38], nine articles were from South Africa [20,22,[39][40][41][42][43][44][45][46], five articles were from Nigeria [18,[47][48][49][50], two studies were from Ghana [51,52], one article was from Kenya [53], three articles were from Tanzania [54][55][56], two studies were from Uganda [21,57] one study was from Burkina Faso [58], and one article was from Zambia [59]. Regarding the study designs, twenty-five (83%) of them were cross-sectional, three studies (3.5%) were cohort and three articles (3.5%) were case-control.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the final review, articles were published from 10 countries among 46 countries were included. Of these studies, eleven studies were found from Ethiopia [13,19,[30][31][32][33][34][35][36][37][38], nine articles were from South Africa [20,22,[39][40][41][42][43][44][45][46], five articles were from Nigeria [18,[47][48][49][50], two studies were from Ghana [51,52], one article was from Kenya [53], three articles were from Tanzania [54][55][56], two studies were from Uganda [21,57] one study was from Burkina Faso [58], and one article was from Zambia [59]. Regarding the study designs, twenty-five (83%) of them were cross-sectional, three studies (3.5%) were cohort and three articles (3.5%) were case-control.…”
Section: Resultsmentioning
confidence: 99%
“…In all studies, alcohol consumption data were taken from the self-report of pregnant women, which means no data was collected using biomarkers or meconium tests. Lists of self-reporting questionnaires were: Alcohol Use Disorder Identification Test-Consumption (AUDIT-C) [22,40,55], Tolerance, Worried, Eye-opener, Amnesia and, K/Cut-down (TWEAK) [57], Alcohol Use Disorders Identification Test (AUDIT) [39,41], Cutting down, Annoyance, Guilt, and Eye-opener (CAGE) [21], Alcohol Smoking and Substance Involvement Test (ASSIST) [44,50], Tolerance-Annoyed, Cut off, Eyeopening (T-ACE) [19], and 1-Question screen strategy [60]. Structured questionnaires were used in the rest of all studies (64%) to screen alcohol consumption during pregnancy.…”
Section: Resultsmentioning
confidence: 99%
“…In this pilot study, 21 mothers and their children with moderate–severe (PAE, as defined by mothers drinking at least twice a week and at least two drinks per occasion during any stage of pregnancy prior to recruitment) and 19 mothers and their children with no alcohol exposure (controls) were assessed for maternal thyroid function and child growth and developmental outcomes ( 61 ).…”
Section: Methodsmentioning
confidence: 99%
“…We have previously reported a high burden of maternal psychosocial risk factors (eg. traumatic stress exposure/posttraumatic stress disorder (PTSD), alcohol and tobacco use); and significant associations between these factors and adverse offspring birth and neurodevelopmental outcomes in this cohort [19][20][21][22][23] . In the current analysis, we aimed to investigate associations between maternal psychosocial risk factors and offspring EA acceleration at birth.…”
Section: Introductionmentioning
confidence: 94%